Impact of Bottom Trawling on Benthic Communities: A Review - B., Meenakumari; Bhagirathan, Usha; P., Pravin (Fishery Technology, 2025)
The detrimental consequences of trawling on the marine environment have always been a matter of great concern. Bottom trawling causes physical and biological damages that are irreversible, extensive and abiding. The present communication intends to focus the impact on benthic communities caused by bottom trawling. The different methodologies used world wide to study the impact of trawling is depicted here. The quantification and characterisation of bycatch will give an ample evidence of impact of bottom trawling. The interpretation of the available historical data of the trawling grounds is also in practice. The experimental trawling brings to light the physico-chemical and biological impacts. The dietary shifts in benthos are an indirect effect of trawling. Bottom trawling imparts both short term and long-term impacts. The long term effects have not been adequately studied as the impacts are ambiguous and are difficult to interpret. In India, studies on impact of bottom trawling has gained momentum by the establishment of Ocean and Atmospheric Sciences and Technology Cell (OASTC) supported by the Ministry of Earth Sciences. These studies have brought to light the impact of trawling on hydrographical parameters and benthic fauna.